1998
DOI: 10.1021/ie970739q
|View full text |Cite
|
Sign up to set email alerts
|

TEOM:  A Unique Technique for Measuring Adsorption Properties. Light Alkanes in Silicalite-1

Abstract: A new and fast technique, the tapered element oscillating microbalance, TEOM, has been applied to accurately measure adsorption in microporous materials at conditions relevant for practical applications. With this technique, the experimental data are not influenced by factors such as buoyancy and flow patterns, which are encountered with conventional gravimetric methods. The equilibrium adsorption of light alkanes, methane, ethane, propane, n-butane, and i-butane in silicalite-1 has been investigated using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
156
3
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(174 citation statements)
references
References 20 publications
14
156
3
1
Order By: Relevance
“…This behavior has not been taken into account in the present work as we deliberately limited the temperature range to 323-723 K. This higher flux has been previously reported [41]. Using a bulk technique in powders, Zhu et al [42] have alleged two adsorption sites for isobutane in silicalite-1. These authors have attributed this low-temperature behavior to isobutane filling of the intersections followed by filling of the zeolite channel.…”
Section: Gas Permeationmentioning
confidence: 71%
See 1 more Smart Citation
“…This behavior has not been taken into account in the present work as we deliberately limited the temperature range to 323-723 K. This higher flux has been previously reported [41]. Using a bulk technique in powders, Zhu et al [42] have alleged two adsorption sites for isobutane in silicalite-1. These authors have attributed this low-temperature behavior to isobutane filling of the intersections followed by filling of the zeolite channel.…”
Section: Gas Permeationmentioning
confidence: 71%
“…Adsorption data employed in this study were obtained from Bakker et al [14] for hydrogen, and Millot et al [41] for isobutane. Comparable results have been obtained for isobutane adsorption in silicalite-1 [42][43][44]. Table 1 gives the membrane geometric parameters and Table 2 the adsorption data in MFI material [14,41] for hydrogen and isobutane, respectively.…”
Section: Composite Membrane Parametersmentioning
confidence: 80%
“…This is in itself not unusual, but in both cases the loading overshoots the 4 molecules per unit cell without an inflection in the isotherm. Many studies, both experimental and computational, have shown that the isotherms of bulky molecules, like isobutane, 11,12,37,38 in MFItype silica show an inflection as the molecules need an extra ''push'' to adsorb in the narrow channels once the 4 intersections per unit cell are occupied. The overshoot can also not be temperature related, since the highest temperature of Song et al is still lower than the lowest temperature of Cavalcante et al, the former being correctly reproduced.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore the single component isotherms of propane and propylene on both NaX and 36 wt% CuCl/NaX were determined using the volumetric technique. Compared to the TEOM (Zhu et al 1998), the volumetric technique allows the measurements of isotherm data at lower pressures and, since the sample is first evacuated before measurement, it is not hindered by the presence of inert gases (e.g. helium or air) inside the pores of the zeolite (Mittelmeijer-Hazeleger et al 2002).…”
Section: Introductionmentioning
confidence: 99%